Widespread and precise reprogramming of yeast protein–genome interactions in response to heat shock - Vinayachandran, Vinesh; Reja, Rohit; Rossi, Matthew J.; Park, Bongsoo; Rieber, Lila; Mittal, Chitvan; Mahony, Shaun; Pugh, B. Franklin (Genome Research, 2018)
Gene expression is controlled by a variety of proteins that interact with the genome. Their precise organization and mechanism of action at every promoter remains to be worked out. To better understand the physical interplay among genome-interacting proteins, we examined the temporal binding of a functionally diverse subset of these proteins: nucleosomes (H3), H2AZ (Htz1), SWR (Swr1), RSC (Rsc1, Rsc3, Rsc58, Rsc6, Rsc9, Sth1), SAGA (Spt3, Spt7, Ubp8, Sgf11), Hsf1, TFIID (Spt15/TBP and Taf1), TFIIB (Sua7), TFIIH (Ssl2), FACT (Spt16), Pol II (Rpb3), and Pol II carboxyl-terminal domain (CTD) phosphorylation at serines 2, 5, and 7. They were examined under normal and acute heat shock conditions, using the ultrahigh resolution genome-wide ChIP-exo assay in Saccharomyces cerevisiae. Our findings reveal a precise positional organization of proteins bound at most genes, some of which rapidly reorganize within minutes of heat shock. This includes more precise positional transitions of Pol II CTD phosphorylation along the 5′ ends of genes than previously seen. Reorganization upon heat shock includes colocalization of SAGA with promoter-bound Hsf1, a change in RSC subunit enrichment from gene bodies to promoters, and Pol II accumulation within promoter/+1 nucleosome regions. Most of these events are widespread and not necessarily coupled to changes in gene expression. Together, these findings reveal protein–genome interactions that are robustly reprogrammed in precise and uniform ways far beyond what is elicited by changes in gene expression.
10.1101/gr.226761.117